Hierarchical Micro/Nano Structures by Combined Self-Organized Dewetting and Photopatterning of Photoresist Thin Films - Sachan, Priyanka (Langmuir : the ACS journal of surfaces and colloids, 2015)
Photoresists are the materials of choice for micro/nanopatterning and device fabrication but are rarely used as a self-assembly material. We report for the first time a novel interplay of self-assembly and photolithography for fabrication of hierarchical and ordered micro/nano structures. We create self-organized structures by the intensified dewetting of unstable thin (∼10 nm to 1 μm) photoresist films by annealing them in an optimal solvent and nonsolvent liquid mixture that allows spontaneous dewetting to form micro/nano smooth dome-like structures. The density, size (∼100 nm to millimeters), and curvature/contact angle of the dome/droplet structures are controlled by the film thickness, composition of the dewetting liquid, and time of annealing. Ordered dewetted structures are obtained simply by creating spatial variation of viscosity by ultraviolet exposure or by photopatterning before dewetting. Further, the structures thus fabricated are readily photopatterned again on the finer length scales after dewetting. We illustrate the approach by fabricating several three-dimensional structures of varying complexity with secondary and tertiary features